2019
DOI: 10.15835/nbha47311599
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Stability and Effects of Plant Growth Regulators for in vitro Propagation of Underutilized Vitis amurensis ‘Cheongsan’

Abstract: Vitis amurensis ‘Cheongsan’ is a plant with high economic value in both medical and agricultural applications. However, its utilization has been restricted owing to difficulties encountered when applying traditional mass propagation methods, requiring instead application of in vitro propagation methods for their mass scale production. Hence, this study was conducted to find the optimal plant growth regulators for shoot multiplication and root induction during in vitro propagation. Among the three cytokinins us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…In contrast, the medium treated with KIN displayed a lower survival rate of 37.8% to 67.4% compared with the cytokinin-containing medium, and it showed no significant difference from the non-treated section without cytokinins. Prior studies on various types of vines have also demonstrated that KINs do not yield favorable results compared with other cytokinin hormones [37,38]. Therefore, the application of various concentrations of KIN in this study did not have a positive effect on the regeneration or sprout induction of 'Shine Muscat' compared with BA and TDZ.…”
Section: Assessment Of the Impact Of Hormones On The Initiation Of Cu...mentioning
confidence: 54%
See 1 more Smart Citation
“…In contrast, the medium treated with KIN displayed a lower survival rate of 37.8% to 67.4% compared with the cytokinin-containing medium, and it showed no significant difference from the non-treated section without cytokinins. Prior studies on various types of vines have also demonstrated that KINs do not yield favorable results compared with other cytokinin hormones [37,38]. Therefore, the application of various concentrations of KIN in this study did not have a positive effect on the regeneration or sprout induction of 'Shine Muscat' compared with BA and TDZ.…”
Section: Assessment Of the Impact Of Hormones On The Initiation Of Cu...mentioning
confidence: 54%
“…In this study, ISSR markers proved to be valuable tools for assessing the genetic fidelity of the in vitro-regenerated plants. The genetic profiles determined using DNA markers demonstrated that genetic fidelity was well-maintained during somatic embryogenesis, with only rare instances of deviation [38]. Moreover, the analysis of the hormonal conditions using ISSR markers revealed no differences between the in vitro-obtained plants and the parental plant, indicating that the hormone treatment used did not lead to significant genetic deviations.…”
Section: Discussionmentioning
confidence: 90%
“…Plants established from ovules at 10 WAP were transplanted to pots filled with a commercial substrate mix and perlite (1:1) contained in plastic sundae cups with lids, and were hardened by gradually lowering the humidity over a period of one month (Kwon et al, 2019). Hardened plants were transferred to a commercial substrate mix in 1 L plastic pots and maintained in the glasshouse.…”
Section: Observation For Occurrence Frequency Of Hypotetraploidsmentioning
confidence: 99%
“…In Korea, many efforts have been made to breed and use new grape cultivars (Park et al, 2017;Kwon et al, 2019;Park et al, 2020;Kim et al, 2020). Researchers of Rural Development Administration in Korea have developed a promising cultivar 'Cheongsoo' by crossing 'Siebel 9110' and 'Himrod' varieties. It has excellent fruit quality and flavor, is suitable for fresh consumption, and has optimal conditions for wine production (Chang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%